2020
DOI: 10.1002/tox.23031
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole attenuates the stemness of nasopharyngeal carcinoma cells via triggering ferroptosis

Abstract: Radiotherapy is a common therapy method for nasopharyngeal carcinoma (NPC) treatment; however, radioresistance greatly limits the clinical efficiency and prognosis of NPC patients. Therefore, it is extremely urgent to reveal the underlying mechanism contributing to radioresistance and find possible diagnostic biomarkers. Here, we collected the spheroids formed by NPC cells, which had been confirmed to hold the stem cell‐like traits, and found that these spheroids exhibited a certain degree of radioresistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…F The expression of stemness markers was examined in the cells described in E. G Sphere-formation ability was evaluated in the cells depicted in E the chemotherapeutic effect [52]. Notably, the previous studies have shown that triggering ferroptosis through another pathway, that is sequestering iron in lysosomes, also can specifically kill CSCs [71,72], this is confirmed by a recent study showing that itraconazole can sequester iron in lysosome and thus trigger ferroptosis, which is essential for itraconazole-mediated attenuation on nasopharyngeal carcinoma spheroid stemness [73]. These results suggest that SLC7A11 might be a potential target for killing CSCs and these above ferroptosis inducers could be used for GC treatments, especially the chemo-resistant tumor types, although in vivo experiments are needed.…”
Section: Discussionmentioning
confidence: 81%
“…F The expression of stemness markers was examined in the cells described in E. G Sphere-formation ability was evaluated in the cells depicted in E the chemotherapeutic effect [52]. Notably, the previous studies have shown that triggering ferroptosis through another pathway, that is sequestering iron in lysosomes, also can specifically kill CSCs [71,72], this is confirmed by a recent study showing that itraconazole can sequester iron in lysosome and thus trigger ferroptosis, which is essential for itraconazole-mediated attenuation on nasopharyngeal carcinoma spheroid stemness [73]. These results suggest that SLC7A11 might be a potential target for killing CSCs and these above ferroptosis inducers could be used for GC treatments, especially the chemo-resistant tumor types, although in vivo experiments are needed.…”
Section: Discussionmentioning
confidence: 81%
“…In colorectal CSCs, knockdown or inhibition of SLC7A11 significantly and specifically kills cancer cells and thus attenuates chemoresistance in CRC ( Xu et al, 2020c ). Besides, two nitroimidazoles ( Koike et al, 2020 ), itraconazole ( Xu et al, 2021 ), and dichloroacetate ( Sun et al, 2021 ) are also proven to have therapeutic potential through promoting ferroptosis in CSCs.…”
Section: Ferroptosis and Cancer Stem Cellsmentioning
confidence: 99%
“…Targeting iron metabolism using the iron nanoparticles can be used to treat cancer through ferroptosis, which has been approved by FDA [32] . Besides, inducing ferroptosis through sequenstering iron in lysosome has been con rmed to speci cally killing CSCs including BCSCs [10,20,22,23] . In this work, we found CPUL119, CPUL129 and CPUL149 could increase the content of iron in breast cancer cells accompanying with the change of iron-regulatory protein such as IRP2, TfR1 and ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been shown that salinomycin and its drivatives could target BCSCs through sequestering iron in lysosomes [19][20][21] . Notably, targeting iron in lysosomes has been con rmed to killing CSCs in other tumors, such as nasopharyngeal carcinoma [22] and colorectal cancer [23] . These results amplify that sequestering iron in lysosomes is a promosing method in targeting BCSCs.…”
mentioning
confidence: 99%